Three-dimensional debulking of eyelids in a case of pachydermoperiostosis: A case report (Indian Journal of Case Reports, 2026)
Pachydermoperiostosis (PDP) is a rare genetic disorder marked by skin thickening, digital clubbing, and periostitis. We present the case of a 53-year-old male with a 20-year history of progressive skeletal changes who developed severe eyelid hypertrophy and ptosis, leading to visual obstruction and cosmetic concerns. Diagnosis was confirmed through clinical findings, imaging, and histopathology. The patient underwent staged surgical correction, including horizontal debulking and levator plication for the upper eyelids, and wedge resections for the lower eyelids. Post-operative results showed a significant reduction in eyelid bulk, improved visual axis, and enhanced facial appearance. Histopathology of the excised tissue revealed sebaceous gland hyperplasia, mucin deposition, and foreign body granulomas, consistent with PDP. This case demonstrates that individualized surgical intervention can effectively manage the functional and aesthetic complications of eyelid involvement in PDP.